Summary and recommendations of a project involving cross-sectional and follow-up studies on the aging worker in Finnish municipal occupations (1981-1985). - Ilmarinen, Juhani; Tuomi, Kaija; Eskelinen, Leena; Nygard, C H; Huuhtanen, P; Klockars, Matti (Scandinavian Journal of Work, Environment & Health, 1991)
This report is a summary of the main findings of 15 studies comprising a multidisciplinary research project. Recommendations are also made on the basis of the findings, and they emphasize the following points: (i) work demands should change with age, (ii) work should be designed for unhealthy people, (iii) work ability should be promoted, (iv) work ability should be regularly monitored, (v) special attention to stress reactions is needed, (vi) knowledge of aging is needed, and (vii) action programs are needed.